On Philosophers' Hallucinations: Naïve Realism and the Master Argument from Hallucination - Mazzullo, Giorgio (2023)
It is widely acknowledged that the Master Argument from Hallucination poses a significant challenge to Naïve Realism, i.e., the view that the phenomenal character of (at least) veridical conscious perceptions is constituted by the obtaining of a relation of perceptual awareness between a subject and aspects of their mind-independent environment. Naïve Realists often attempt to resist the argument by maintaining that the possibility of the hallucinatory events invoked by the argument is compatible with their view. However, this approach has led to some views of visual experiences that many have considered implausible. My work assesses the prospects for Naïve Realists to resist the Master Argument by rejecting the possibility of such hallucinatory events, i.e., Philosophers’ Hallucinations construed as non-naïve realist experiences. This thesis is divided into two parts. The first part outlines Naïve Realism and presents the Master Argument from Hallucination, emphasising the crucial role that the possibility of such hallucinatory events plays in the argument. The second part assesses the Eliminativist strategy. I present four Eliminativist strategies to resist the argument: the Irreproducibility Strategy, the Non-Replicability Strategy, the Distinguishability Strategy, and the Monist Strategy. Based on extant proposals, I argue that none of them are viable in their current form. In the final chapter, I present a more promising way to implement the Eliminativist Strategy. I propose that Philosophers’ Hallucinations should be construed as naïve realist experiences. In undergoing such mental events, one would be perceptually aware of a region of space. This approach allows Naïve Realists to reject the possibility of Philosophers’ Hallucinations construed as non-naïve realist experiences and, therefore, reject the Master Argument from Hallucination.